Identification of Compressibility Rate and Expansion Index on the Physical Characteristics of Peat Soil - Dora Melati Nurita Sandi, Lulu Adiya Salsabila (Jurnal Handasah, 2025)
ABSTRACT Peat soils have very high pore numbers and moisture content, so their bearing capacity is very low and their compressibility is very high. If it receives a load, it will decrease greatly over a relatively long period of time. Therefore, it is necessary to identify the characteristics of the Ambarawa peat soil due to the different properties of the peat soil in each location, the ability to shrink and the low bearing capacity. The purpose of this study was to determine the physical characteristics, compressibility velocity and development index of Ambarawa peat soil. By using laboratory testing methods in the form of testing soil physical properties including moisture content, specific gravity, fiber content, ash content, pH content and soil mechanical testing including consolidation testing to obtain the compressibility index and development index values. The laboratory test results showed that the moisture content was 410,58%, the specific gravity (Gs) was 1,20, the ash content was 48,143%, the organic content was 51,9%, the pH was 6,6, and the Ambarawa peat was a medium mature peat (hemic) with a fiber content of 56,16%. Sample 1 had a compressibility index (Cc) of 0,430764 and a development index (Cs) of 0,00632. Sample 2 has a compressibility index (Cc) value of 0,430182 and a development index (Cs) of 0,0025. With a percentage difference of Cc of 0,135% and a percentage difference of Cs of 60,44%.